Wolf warrior 2 [videorecording (DVD)] - Wu, Jing, 1974-; Wu, Jing, 1974-; Grillo, Frank, 1963-; Jade, Celina, 1985- (Well Go USA Entertainment, 2017)
With his career in tatters, China's deadliest Special Forces operative has settled into a quiet life on the sea. But when he crosses paths with a sadistic band of mercenaries terrorizing innocent civilians, he must reaffirm his duty as a soldier and save the day once again.